A novel cytotherapy device for rapid screening, enriching and combining mesenchymal stem cells into a biomaterial for promoting bone regeneration. Issue 1 (December 2017) - Zhuang, Yifu; Gan, Yaokai; Shi, Dingwei; Zhao, Jie; Tang, Tingting; Dai, Kerong
Abstract Bone defects are a common challenge in clinic, usually warranting bone grafts. However, current strategies to obtain effective graft materials have many drawbacks. Mesenchymal stem cell (MSC)-based therapy is a promising alternative. We designed an innovative appliance named the stem cell screen–enrich–combine(-biomaterials) circulating system (SECCS). In this study, 42 patients who required bone graft underwent SECCS-based treatment. Their bone marrow samples and beta-tricalcium phosphate (β-TCP) granules were processed in the SECCS for 10–15 minutes, to produce MSC/β-TCP composites. These composites were grafted back into bone defect sites. The results showed 85.53% ± 7.95% autologous MSCs were successfully screened, enriched, and seeded on the β-TCP scaffolds synchronously. The cell viability remained unchanged after SECCS processing. Clinically, all patients obtained satisfactory bone healing. Thus, withoutin vitro culture, the SECCS can produce bioactive MSC/β-TCP composites for bone regeneration during surgery. The SECCS represents a convenient, rapid, low-cost, and safe method for bone regeneration.